ENTREPRENEURSHIP INTENTION BASED ON MODIFIED THEORY OF PLANNED BEHAVIOR - Bernadetta Diansepti Maharani; Lusia Tria Hatmanti Hutami (Management Department, Faculty of Economics and Business, Universitas Jambi, 2019)
The current phenomenon of the number of workforce is not compatible to the available jobs. Based on this phenomenon the workforce should be able to read opportunities for entrepreneurship. This study aims to determine the intentions of students in entrepreneurship by using Theory of Planned Behavior. In addition, the purpose of this study is to be able to know the interest of the millennial generation in entrepreneurship and to be able to find out various factors that can influence the interest of the millennial generation for entrepreneurship. The sampling method used convenience sampling and overall, sample of this study is 190 students in Yogyakarta who have been taking entrepreneurship courses and the selling class. The method used is regression analysis and descriptive using SPSS. The result showed that all of the hypotheses are accepted. Therefore, it strengthen assumption that millennial generation has an interest to the entrepreneurship, then, early education should be completed with hard skill and soft skill as a whole complement to the scholar